Perancangan Sistem Penyemprotan Gulma Otomatis Berdasarkan Deteksi Citra Gulma Berbasis IoT - Nailul Muna; Nanang Syahroni; Karimatun Nisa; Natty Novia Ramadhani; Dimas Ade Firmanda (AI Society & STMIK Indonesia, 2024)
Effective weed management is crucial in agriculture to improve crop yields and reduce the environmental impact of pesticide use. This research proposes the implementation of an Internet of Things (IoT)-based weed detection system for real-time weed spraying. The system integrates image detection technology with IoT to automatically monitor weeds. Cameras connected through IoT capture images of agricultural areas and perform image processing using image processing. Once the weeds are detected, the system controls a pesticide sprayer with precision, targeting the areas affected by weeds, utilizing ultrasonic and water flow sensors to monitor the pesticide and water volumes used for spraying. The results of the system can be monitored through an application. Testing results show that the pump is capable of spraying based on the weed detection outcome, the system’s End-to-End Process time measured at an average of 33.6 seconds when weeds are detected and 30 seconds when no weeds are detected.